2009
DOI: 10.1211/jpp.61.01.0018
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic comparison of puerarin after oral administration of Jiawei-Xiaoyao-San to healthy volunteers and patients with functional dyspepsia: influence of disease state

Abstract: There were statistically significant differences in the pharmacokinetic parameters of puerarin including the values for Cmax, AUC0-360, Cl/F and MRT0-360 between healthy volunteers and patients with functional dyspepsia. The pharmacokinetic parameters showed that functional dyspepsia reduced the absorption of puerarin after oral administration of Jiawei-Xiaoyao-San.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 31 publications
(12 citation statements)
references
References 11 publications
(23 reference statements)
0
12
0
Order By: Relevance
“…The most common cause of angina is CHD (5) and ~50% of patients with the disease exhibit chronic stable angina as their initial symptom (6). Recent studies have indicated that angina is one of the disease states that may modify the pharmacokinetics of a drug (7–9). However, the pathway by which angina is regulated by the pharmacokinetics of traditional Chinese medicine is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…The most common cause of angina is CHD (5) and ~50% of patients with the disease exhibit chronic stable angina as their initial symptom (6). Recent studies have indicated that angina is one of the disease states that may modify the pharmacokinetics of a drug (7–9). However, the pathway by which angina is regulated by the pharmacokinetics of traditional Chinese medicine is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Of over 128 papers reporting the pharmacokinetics of TCM in MEDLINE [MeSH terms: pharmacokinetics and human and (decoction or herbs or TCM) and English], only 1 involved patients (Qin et al, 2009). Therefore, the clinical pharmacokinetic study of TCM should be a topic of study in the future.…”
Section: Discussionmentioning
confidence: 99%
“…55 55 recently performed a literature review, identified 14 randomized controlled studies in which MXS was used alone or compared with a prokinetic agent, but was unable to draw a conclusion about its efficacy because all studies were of poor quality.…”
Section: Modified Xiaoyao Sanmentioning
confidence: 99%